Batch and fixed bed adsorption studies of lead (II) cations from aqueous solutions onto granular activated carbon derived from mangostana garcinia shell - Chowdhury, Z.Z.; Khalid, K.; Rafique, R.F.; Khan, R.A.; Zain, Sharifuddin Md (2012)
The feasibility of granular activated carbon (GAC) derived from Mangostene (Mangostana garcinia) fruit shell to remove lead, Pb 2+ cations was investigated in batch and fixed bed sorption systems. Batch experiments were carried out to study equilibrium isotherms, kinetics, and thermodynamics by using an initial lead (Pb 2+ ions) concentration of 50 to 100 mg/L at pH 5.5. Equilibrium data were fitted using Langmuir, Freundlich, and Temkin linear equation models at temperatures 30°C, 50°C, and 70°C. Langmuir maximum monolayer sorption capacity was 25.00 mg/g at 30°C. The experimental data were best represented by pseudo-second-order and Elovich models. The sorption process was found to be feasible, endothermic, and spontaneous. In column experiments, the effects of initial cation concentration (50 mg/L, 70 mg/L, and 100 mg/L), bed height (4.5 cm and 3 cm), and flow rate (1 mL/min and 3 mL/min) on the breakthrough characteristics were evaluated. Breakthrough curves were further analyzed by using Thomas and Yoon Nelson models to study column dynamics. The column was regenerated and reused consecutively for four cycles. The result demonstrated that the prepared activated carbon was suitable for removal of Pb 2+ from synthetic aqueous solution using batch, as well as fixed bed sorption systems.